Dandy–Walker Malformation: is the 'tail sign' the key sign?. (17th November 2015) - Bernardo, Silvia; Vinci, Valeria; Saldari, Matteo; Servadei, Francesca; Silvestri, Evelina; Giancotti, Antonella; Aliberti, Camilla; Porpora, Maria Grazia; Triulzi, Fabio; Rizzo, Giuseppe; Catalano, Carlo; Manganaro, Lucia
Abstract: Objective: The study aims to demonstrate the value of the 'tail sign' in the assessment of Dandy–Walker malformation. Methods: A total of 31 fetal magnetic resonance imaging (MRI), performed before 24 weeks of gestation after second‐line ultrasound examination between May 2013 and September 2014, were examined retrospectively. All MRI examinations were performed using a 1.5 Tesla magnet without maternal sedation. Results: Magnetic resonance imaging diagnosed 15/31 cases of Dandy–Walker malformation, 6/31 of vermian partial caudal agenesis, 2/31 of vermian hypoplasia, 4/31 of vermian malrotation, 2/31 of Walker–Warburg syndrome, 1/31 of Blake pouch cyst and 1/31 of rhombencephalosynapsis. All data were compared with fetopsy results, fetal MRI after the 30th week or postnatal MRI; the follow‐up depended on the maternal decision to terminate or continue pregnancy. In our review study, we found the presence of the 'tail sign'; this sign was visible only in Dandy–Walker malformation and Walker–Warburg syndrome. Conclusion: The 'tail sign' could be helpful in the difficult differential diagnosis between Dandy–Walker, vermian malrotation, vermian hypoplasia and vermian partial agenesis. © 2015 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? US examination may allow the prenatal diagnosis of most cerebellar malformations however the differential diagnosis of cerebellar abnormalities is limited by 2D–3D approaches, due to the complicated imaging of this region and overall the pons. What Does This Study Add? Fetal MR can represent an useful imaging technique in order to confirm and characterize the different cerebellar malformation thanks to the multiplanes orientation which allows to study biometry and morphology of all the structures involved and the "tail sign" may allow a differential diagnosis between vermian malrotation and DW malformation particularly in early stage (19–24 weeks of gestation).